Agility performance in athletes of different sport specializations - Zemkova, E.; Hamar, D. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2014)
Data on agility skills in different populations using pre-planned, change of direction speed tests have previously been reported. However, there are no available data on the agility times of athletes specializing in different sports obtained from Reactive agility tests. Objective: The study compares agility time in groups of athletes of different sports where agility is one of the limiting factors of performance. Methods: Altogether 282 athletes of 14 sport specializations performed the Agility test. Their task was to touch, as fast as possible, with either the left or the right foot, one of four mats located outside each of the four corners of a 0.8 m square. The mats had to be touched in accordance with the location of a stimulus in one of the corners of a screen. The test consisted of 60 visual stimuli with random generation of their location on the screen and a time of generation of 500 to 2,500 ms. The result was a sum of the 32 best agility times. Results: The Agility test has been found to be sensitive in distinguishing groups of athletes of different sport specializations. Table tennis players, badminton players, fencers, tae-kwon-do competitors and karate competitors showed the best agility times (< 350 ms), followed by ice-hockey, tennis, soccer, volleyball, basketball, and hockeyball players (350-400 ms), then aikidoists (400-450 ms), and finally judoists and wrestlers (450-500 ms). Conclusions: The best agility times are in athletes of racquet sports, followed by competitors of combat sports with reactions to visual stimuli, then players of ball sports, and finally competitors of combat sports with reactions to tactile stimuli. Since this is the first study testing agility skills using the Reactive agility test in athletes of different sport specializations, data obtained can be used for comparison of athletes within particular sports.